2020
DOI: 10.6008/cbpc2179-6858.2020.002.0036
|View full text |Cite
|
Sign up to set email alerts
|

Perfil socioeconômico e conhecimento de guias-piloteiros da bacia do médio Rio Negro, Amazonas

Abstract: Na Amazônia, o município de Barcelos tem se destacado como um dos principais destinos para quem pratica a pesca esportiva. O objetivo do presente estudo foi descrever o perfil socioeconômico e o conhecimento sobre a legislação de pesca esportiva de pilotos-guia da Bacia do Médio Rio Negro, Amazonas. Foram realizadas entrevistas semiestruturadas, utilizando questionários com orientadores (N= 55), no período de janeiro de 2016 a maio de 2019. A média de idade dos orientadores foi de 42 anos, com faixa etária de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
0
0
1
Order By: Relevance
“…The mean age found was 48 years, thus corroborating the study by Ladislau et al (2020), Sobreiro (2007), Inomata and Freitas (2015a) and Ribeiro et al (2020), who reported the mean age of 42, 45, 45 and 42 years, respectively. According to the study by Zacardi et al (2017), this trend is justified in view of the scenario that young people may be prioritizing studies and/or directing their occupations to other activities, considered by most of them of greater importance than fishing activity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The mean age found was 48 years, thus corroborating the study by Ladislau et al (2020), Sobreiro (2007), Inomata and Freitas (2015a) and Ribeiro et al (2020), who reported the mean age of 42, 45, 45 and 42 years, respectively. According to the study by Zacardi et al (2017), this trend is justified in view of the scenario that young people may be prioritizing studies and/or directing their occupations to other activities, considered by most of them of greater importance than fishing activity.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, there was a predominance of male fishers, although there was also the presence of women in the activity, indicating that the activity does not have a unilateral character. The study of Ladislau et al (2020) described the presence of men and women in the activity, although the male presence is predominant, corroborating with Sobreiro (2007), Freitas (2015a), andRibeiro et al (2020). The high proportion of male fishers is related to the cultural aspect, in which the head of the family is responsible for family sustenance (Sá-Oliveira et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Porém, alguns pescadores também são polivalentes, exercendo mais de uma modalidade de pesca e em determinados períodos trabalham como piloteiro, conhecidos como guia de pesca esportiva, e pescador comercial (WITKOSKI, 2007;FERREIRA et al, 2017;LADISLAU et al, 2019). Além disso, podem atuar em outros campos como vendedor de peixes, camareira e cozinheira de barco hotel (excursões de pesca esportiva), auxiliar de pedreiro, com artesanato, com agricultura, comércio de farinha e outros produtos alimentícios, e transporte em pequenas embarcações (BELTRÃO et al, 2009;SOUZA et al, 2009;LADISLAU et al, 2019;RIBEIRO et al, 2020).…”
Section: Pescador Ornamentalunclassified